IMPORTANCE OF TROPONIN AND B-TYPE NATRIURETIC PEPTIDE TESTS IN HEART DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The heart is a muscular, fist-sized organ located within your chest in a space between the two lungs (mediastinum). The heart continuously pumps blood, beating as many as 100,000 times a day. The blood that the heart moves carries oxygen and nutrients throughout the body and transports carbon dioxide and other wastes to the lungs, kidneys, and liver for removal. In cases of heart muscle damage due to various causes, several laboratory tests are required. This article will review some of them.